Production of autologous platelet-rich plasma from an animal model - Buyong, Zunariah; A.Talib, Norlelawati; Ab Rahman, Jamalludin; Khalid, Kamarul Ariffin; Zakaria@Mohamad, Zamzuri; Zulkifly, Ahmad Hafiz; Abdel Wahab, Emad Mohamad Nafie (2010)
There has been recent interest regarding the role of autologous platelet-rich plasma (PRP) on soft and hard tissue healing. Inactivated platelets contain various growth hormones that involve in tissue healing such as platelet-derived growth hormone (PDGF), vascular ndothelial growth hormone (VEGF), transforming growth factor-ß (TGF-ß), epidermal growth factor (EGF) and insulin-like growth factor (IGF). Upon activation, platelets release these hormones from its α-granule. PRP concentration of three to five-fold the baseline level or the count above 1,000,000/ml was shown the ability to promote tissue healing. Even though the protocol for the production of PRP from a large amount of blood has been established in human, the method could not be adopted in animal studies, which require small amount of blood. Lack of method’s standardization in PRP preparation has also contributed to the difficulty of getting sufficient PRP for experimental studies. Here, we presented a double-centrifugation technique for the production of autologous PRP from rabbit’s blood.